Pengembangan Game Edukasi Pengetahuan Sampah Organik dan Non Organik pada Kegiatan P5 Kelas IV Sekolah Dasar - Putri, Sherly Dwi; Anugrah, Septriyan; Hendri, Nofri; Rahmayanti, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to develop educational game products for use in learning. This research uses the Research and Development (R&D) development method with a 4D development model which consists of 4 stages, namely define, design, development and disseminate. The validity test was carried out by 3 experts, namely 1 material expert validator and 2 media expert validators. Based on validity tests by material experts, results were obtained with a percentage of 85.4% in the valid category. The results of the validity test with media expert I and media expert II obtained a percentage of 96% with a very valid category. The practicality test results obtained a percentage of 95% in the very practical category. Based on the results of validity and practicality, it can be concluded that the educational games in Activity P5 are valid and practical to use in learning